UJI LAMA PERENDAMAN BENIH MAHONI (Swietenia mahagoni) MENGGUNAKAN AIR DAUN SIRIH (Piper betle Linn.) DALAM MENJAGA KUALITAS BENIH - Arie Febriyan Rianto; M. Mardhiansyah; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Swietenia mahagoni is thetype of plant that fast growing. Swietenia mahagoni usefull ranging from seeds, leaves and stems. Society in general just let Swietenia mahagoni seeds to grow naturally without treatment to the seeds. The best seed treatment is by using plants that contain a disinfectant or antiseptic and easly found around the environment, including the Piper betle Linn. This study aimed to determined the soaking effect of Swietenia mahagoni seeds in Piper betle Linn. water toward of seed quality and determined the best time term of long soaked seeds in Piper betle Linn. water to keep seed quality. This research compiled in a Completely Randomized Design (CRD) with 4 treatment and 4 replications. Treatment consists of soaking the seeds for 10 minutes, 20 minutes, 30 minutes and 40 minutes. Data were analyzed by Analysis Of Variance (ANOVA), than continued with DNMRT double distance test at 5% level. The result showed that the soaking of Swietenia mahagoni seeds affect the quality of seeds, proved by the percentage of seeds germinated better. The best seed soaking times is 40 minutes with the percentage of germination 85,5%, speed germination 14,98 days and seedling height 11,29 cm.Keywords: Swietenia mahagoni, Piper betle Linn., Seed Quality